COMMISSIVE SPEECH ACT IN THE FIRST DEBATE OF JAKARTA GOVERNOR ELECTION 2017 - INTEN, LIESTYORINI (LANTERN (Journal on English Language, Culture and Literature), 2017)
This research focuses on analyzing commissive speech acts by using Vanderveken’s theory (1990). The study aim at 1) classifying the commissive type conducted in the debate of governor election Jakarta, and 2) explaining the illocutionary forces of it. It is conducted in order to know how the candidates using commissive speech act while giving their speech. The type of research is descriptive qualitative. In analyzing the data, the writer took note and classified the commissive type. The study shows that there are five types of commissive out of seven, they are promise, guarantee, threathen, volunteer, refuse. Each candidate shows different styles of explaining their vision and mission. There are sixteen data, but only several data were explained due to similarity of several types.